Short-term effect of different time interval between self-expanding metallic stent and surgery for left-sided malignant colorectal obstruction - Zhang, Jiawei; Su, Mingli; Lin, Dezheng; Zhong, Qinghua; Hu, Jiancong; Deng, Jiaxin; Lv, Miwei; Xu, Tian; Li, Juan; Guo, Xuefeng (Frontiers in Gastroenterology, 2022)
Background The optimal time interval between self-expanding metallic stent (SEMS) placement and surgery in patients with left-sided malignant colorectal obstruction (LMCO) remains controversial. Intestinal obstruction and SEMS placement would lead to intestinal edema, local tumor infiltration, and fibrosis, which may have a certain impact on elective surgery. Although prolong time interval would reduce relative complications, the risk of tumor progression must be taken into account. Therefore, our study proposes whether there is a difference in short-term postoperative complication outcomes between waiting for an interval of ≤4weeks compared with an extended interval for neoadjuvant chemotherapy followed by surgery. Methods All patients who underwent SEMS placement as BTS treatment for LMCO between January 2012 and December 2021 were retrospectively identified. The primary outcomes of this study were short-term clinical postoperative complications (Clavien-Dindo grading ≥II). Results Of the 148 patients, 70.27% of patients underwent surgery ≤4 weeks of SEMS placement (Group 1) while 29.73% of patients underwent surgery >4 weeks of SEMS placement (Group 2). After SEMS placement, the patients in Group 2 received neoadjuvant chemotherapy and then elective surgery. Significant differences were observed between both groups (Group 2 vs Group 1) for postoperative complications (Clavien-Dindo grading ≥II, 2.3% vs 14.4%, p=0.040), postoperative bowel function time (p<0.001), postoperative hospital stay (p=0.028) and total hospital stay (p=0.002). Conclusions A bridging interval of >4 weeks between SEMS placement and surgery for LMCO has better short-term clinical outcome.